The Effect of Using Interactive E-Module on Student Motivation and Learning Outcomes on Acid-Base Solution Material - Simanjuntak, Maria Enjellita; Nainggolan, Bajoka (Universitas Lampung, 2023)
Abstract:The Effect of Using Interactive E-module on Student Motivation and Learning Outcomes on Acid-Base Solution Material . The problem in this study is the low motivation and learning outcomes of chemistry students on acid-base solution material. This study aims to determine the effect of project-based learning (PjBL) model assisted by interactive e-module media on student motivation and learning outcomes at SMAN 7 Medan. The research sample was taken 2 classes with random sampling technique and taught with PjBL model. The treatment in the experimental class was assisted by interactive e-module while the control class was assisted by student packet books. Data collection used test instruments and questionnaires. The results showed that the average learning outcomes of experimental class students were 84.43 with a gain of 68.64% and the control class was 78.71 with a gain of 53.68%. Student learning motivation in the experimental class was 81.71 while in the control class it was 75.29. There is a significant correlation with a medium category between motivation and student learning outcomes of 19.36%. The hyphoteses of this study were accepted, namely there is an effect of the PjBL model assisted by interactive e-module media on student chemistry learning outcomes, student chemistry learning motivation, and there is a correlation between learning motivation and student learning outcomes.Keywords: E-module, Project Based Learning (Pjbl),Learning Outcomes ,Student Motivation,Acid-Base Solution.DOI: 10.23960/jppk.v12.i3.23.04